Penyuluhan Program Pendidikan Anti Korupsi di SMP untuk Membentuk Generasi Muda yang Integritas - Adiyono Adiyono; Mardani Mardani; Ahmad Fauzan; Ali Maftuuh Mutaqiin; Aqil Dhiya Ulhaq; Hasan Mustofa Al-Baihaq; Romdani; Indra Gunawan (CV Putra Publisher, 2023)
Community service activities are carried out by the PKM Team of STIT Ibnu Rusyd Tanah Grogot PAI Study Program by choosing a theme that attracts the attention of many people today, including students. The number of corruption cases that occur in society encourages the PPM team to provide knowledge about the crime of corruption and its legal arrangements to prevent students from being affected by acts that lead to criminal acts of corruption in various forms, therefore the PKM team chose the theme of